RANCANG BANGUN APLIKASI PENILAIAN KINERJA BERBASIS WEB PADA PABRIK GULA TJOEKIR KABUPATEN JOMBANG - Anggraini, Nuriva; Nurcahyawati, Vivine; Rahmawati, Endra (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2020)
The Tjoekir Sugar Factory is a subsidiary of the company of PT Perkebunan Nusantara X with its main business being the production of sugar which is located on the road of Irian Jaya, Cukir, Jombang, East Java. The Tjoekir Sugar Factory has 206 employees. every year the employee has a performance appraisal to find out the performance of each employee. Measuring employee performance is done in each unit by using the key performance indicator method. The assessment has several problems, one of which is the result of an inaccurate calculation of employee performance appraisal, so the human resources must re-calculate to justify the calculation. Based on the existing problems, the Tjoekir Sugar Factory requires a performance appraisal application using the key performance indicator method that can support the performance appraisal process of the Tjoekir Sugar Factory employee. The developed application can help several units (human, plant, processing, installation, financial, general resources and quality control) in the performance appraisal process. The design of employee performance appraisal applications developed can help the general manager, managers, assistant managers and young assistants in the process of data processing, assessing and evaluating appraisals and making employee performance appraisal reports.